Analysis of Economic Growth Rates in East Java During the Covid-19 Period - Drajat, Estu Unggul (Journal of Economics and Social Sciences (JESS), 2023)
Introduction/Main Objectives: This study aims to determine economic growth during the Covid-19 period in East Java for 2019-2021. Research Methods: This study used a qualitative method using a library research approach. Finding/Results: Based on the study's results, economic growth during the Covid-19 period in East Java for the 2019-2021 period experienced a drastic decline. In quarter IV-2020 against quarter IV-2019 (y-on-y), East Java's economy contracted by 2.64 percent. In the first quarter of 2020, growth began to slow down to 2.97 percent. Furthermore, in the second quarter of 2020, it contracted to 5.98 percent compared to the second quarter of 2019. And in the second quarter of 2021, economic conditions began to improve even though they were still contracting, namely by 7.05 percent. Conclusion: The government must be able to provide policies that can increase economic growth because economic growth is a reference for the level of social welfare in real terms.